OCT‐assessment of scaffold resorption: Analysis of strut intensity by a new resorption index for poly‐l‐lactic acid bioresorbable vascular scaffolds. Issue 7 (3rd April 2019) - Blachutzik, Florian; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Boeder, Niklas; Doerr, Oliver; Weissner, Melissa; Bauer, Timm; Nef, Holger; Hamm, Christian; Schlundt, Christian
Abstract: Background: The aim of this study was to analyze individual differences in resorption of bioresorbable vascular scaffolds (BRS) through optical coherence tomography (OCT) analysis and to identify factors potentially influencing the resorption process. Methods: Between April 2016 and July 2017 clinically driven invasive coronary angiography and OCT examinations were performed in 36 patients who had previously been treated with a total of 48 BRS (ABSORB BVS, Abbott Vascular, Santa Clara, CA). For each scaffold, a new BRS‐RESORB‐INDEX (BRI) was calculated. Results: The mean time interval since implantation was 789 ± 321 days. In OCT, BRS struts remained detectable in all 48 BRS. Normalized light intensity as a marker for the resorption of BRS struts increased with time in a linear fashion (Spearman Rho: p < .001, correlation coefficient = .90; R 2 [linear] = .91). Multivariable analysis identified diabetes (BRI of patients with diabetes vs. patients without diabetes: 0.34 ± 0.13 vs. 0.58 ± 0.22; p = .002) and presence of Peri‐strut low intensity areas (PSLIA, BRI of 10 patients with PSLIA vs. 26 patients without PSLIA: 0.44 ± 0.21 vs. 0.61 ± 18; p = .027) as independent predictors for a prolonged BRS resorption, whereas the resorption rate in ACS patients (STEMI, NSTEMI, and unstable angina; n = 13) was significantly higher as compared to patients without ACS (0.62 ± 0.17 vs. 0.43 ± 0.24; p = .012). Conclusion: In humans, BRS resorption rate is significantly influenced by numerous factors. Our data suggest that diabetes and PSLIA are associated with a prolonged resorption process, whereas in ACS patients, BRS resorption appears to be significantly faster.